Investigation on interferometric pH sensor for in-vivo application. - Boo, Maggie. (2013)
In this report, a detailed description on the fabrication of an optical pH sensor is presented. The report would first cover some background information and discuss the fabrication process followed by the results of analyzing the fabricated sensor. Finally, the report will be concluded with a summary of work done and discuss some of the future works and recommendations to further improve its potential as a pH sensor. The proposed sensor is based on the Fabry-Perot interferometry sensing mechanism which utilizes the interference between two or more beams that have travelled through different optical paths. The proposed sensor would be fabricated by splicing a small segment of hollow core fiber between two single mode fiber, coated using the layer-by-layer electrostatic self-assembly technique and analysed for its potential in pH sensing. The analysing results proved that it is most sensitive to a pH range of 7.00 to 8.00 and has good sensitivity when tested under different salt concentrations. It also has a robust time response of less than five minutes and is proved to be insensitive to temperature.